The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1017/s0007485315000310
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistics as a tool to study mite dispersion in physic nut plantations

Abstract: Spatial distribution studies in pest management identify the locations where pest attacks on crops are most severe, enabling us to understand and predict the movement of such pests. Studies on the spatial distribution of two mite species, however, are rather scarce. The mites Polyphagotarsonemus latus and Tetranychus bastosi are the major pests affecting physic nut plantations (Jatropha curcas). Therefore, the objective of this study was to measure the spatial distributions of P. latus and T. bastosi in the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 45 publications
(65 reference statements)
1
28
1
1
Order By: Relevance
“…The number of mites was relatively low when compared to other studies performed in the state of Tocantins (Table 1) (SARMENTO et al, 2011;CRUZ et al, 2012;2013a;2013b;ROSADO et al, 2014;ROSADO et al, 2015a). However, a study performed during the same agricultural year (2011/2012) as the present study (SARAIVA et al, 2015) also observed a low occurrence of phytophagous and predatory mites associated with J. curcas.…”
Section: Resultscontrasting
confidence: 60%
See 3 more Smart Citations
“…The number of mites was relatively low when compared to other studies performed in the state of Tocantins (Table 1) (SARMENTO et al, 2011;CRUZ et al, 2012;2013a;2013b;ROSADO et al, 2014;ROSADO et al, 2015a). However, a study performed during the same agricultural year (2011/2012) as the present study (SARAIVA et al, 2015) also observed a low occurrence of phytophagous and predatory mites associated with J. curcas.…”
Section: Resultscontrasting
confidence: 60%
“…However, a study performed during the same agricultural year (2011/2012) as the present study (SARAIVA et al, 2015) also observed a low occurrence of phytophagous and predatory mites associated with J. curcas. This indicates seasonal dynamics for both predatory and phytophagous mite populations of J. curcas (ROSADO et al, 2015a).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Populations of insect pests in crops can be estimated using interpolation procedures, which allow generating continuous surfaces through specific sampling units (Soares et al, 2008;Duarte et al, 2015). Among the interpolation methods, ordinary kriging is one of the most used (Sciarretta & Trematerra, 2014;Rosado et al, 2015). In it, theoretical semivariogram models are fit to the experimental ones, in order to find the best model -with the smallest errors -for each data set (Pasini et al, 2014).…”
Section: Introductionmentioning
confidence: 99%